Antibacterial and Antibiofilm Activities of Psychorubrin, a Pyranonaphthoquinone Isolated From Mitracarpus frigidus (Rubiaceae) - Lemos, Ari S. O.; Campos, Lara M.; Melo, Lívia; Guedes, Maria C. M. R.; Oliveira, Luiz G.; Silva, Thiago P.; Melo, Rossana C. N.; Rocha, Vinícius N.; Aguiar, Jair A. K.; Apolônio, Ana C. M.; Scio, Elita; Fabri, Rodrigo L. (Frontiers in Microbiology, 2018)
Psychorubrin, a natural pyranonaphthoquinone found in different plants, has become an interesting compound in the search for new antimicrobial therapeutic agents. Here, we investigated the potential antagonistic activity of psychorubrin against planktonic and biofilm bacteria. First, psychorubrin was tested against several Gram-positive and Gram-negative bacteria strains by a broth microdilution susceptibility method. Second, bacterial killing assay, bacterial abundance, and membrane viability were evaluated. The nucleotide leakage assay was used to verify membrane destabilization while antibiofilm activities were analysed by the effect on established biofilm, static biofilm formation, isolation of biofilm matrix assay and scanning electron microscopy. In parallel, the combinatorial effect of psychorubrin and chloramphenicol was evaluated by the checkerboard method. Psychorubrin was active against Gram-positive bacteria, showing rapid time-dependent kinetics of bacterial killing, amplified nucleotide leakage, and greater activity against the methicillin-resistant species (MRSA) Staphylococcus aureus 33591 and 33592 and Staphylococcus pyogenes 10096. Psychorubrin also interfered with the composition of the biofilm matrix by reducing the total content of carbohydrates and proteins. A synergic effect between psychorubrin and chloramphenicol was observed for S. aureus 33592 and S. pyogenes 10096 while an additive effect was detected for S. aureus 33591. Our findings demonstrate, for the first time, an antagonistic activity of psychorubrin against bacteria not only in their planktonic forms but also in biofilms, and identify bacterial membranes as primary targets for this compound. Based on these observations, psychorubrin has a good potential for the design of novel antimicrobial agents.